Executive control of bureaucracy and presidential cabinet appointments in East Asian democracies - Lee, Don S. (Wiley, 2018)
This article examines the role of cabinet appointments in controlling the bureaucracy in presidential democracies. I demonstrate how administrative challenges stemming from the structure of the bureaucracy shape presidential choice of ministers. Analyzing a sample of four East Asian cases from 1986 through 2013, I find that presidents are more likely to select ministers from the civil service as bureaucracies are more professionalized, controlling for several political factors. Further evidence from qualitative interviews and case studies suggests that, in professionalized systems equipped with a sizable pool of talent but lacking responsiveness, presidents tend to promote ideologically aligned senior civil servants. However, in politicized systems, where presidents easily obtain responsiveness but face a low level of competence, policy experts tend to be selected from outside the bureaucracy. My findings have important implications for the regulatory governance and state capacity of East Asia, demonstrating the value of balancing between responsiveness and competence.